Review of skin dose calculation software in interventional cardiology. (December 2020) - Malchair, Françoise; Dabin, Jérémie; Deleu, Marine; Merce, Marta Sans; Bjelac, Olivera Ciraj; Gallagher, Aoife; Maccia, Carlo
Highlights: Critical analysis of available Skin Dose Calculation (SDC) software tools. Patient radiation protection in relation to skin dose in interventional cardiology. Review of SDC capabilities to display dose distribution. Abstract: Purpose: In interventional cardiology, patients may be exposed to high doses to the skin resulting in skin burns following single or multiple procedures. Reviewing and analysing available software (online or offline) may help medical physicists assessing the maximum skin dose to the patient together with the dose distribution during (or after) these procedures. Method and results: Capabilities and accuracy of available software were analysed through an extensive bibliography search and contacts with both vendor and authors. Their markedly differed among developers. In total, 22 software were identified and reviewed according to their algorithms and their capabilities. Special attention was dedicated to their main features and limitations of interest for the intended clinical use. While the accuracy of the 12 software products validated with measurements on phantoms was acceptable (within ± 25%), the agreement was poor for the two products validated on patients (within ± 43% and ± 76%, respectively). In addition, no software has been validated on angiographic units from all manufacturers, though several software developers claimed vendor-independent transportability. Only one software allows for multiple procedures dose calculation. Conclusion: Large differences among vendors made it clear that work remains to be done before an accurate and reliable skin dose mapping is available for all patients.